2017
DOI: 10.1111/jfs.12394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ziziphora clinopodioides essential oil on shelf life and fate of Listeria monocytogenes and Staphylococcus aureus in refrigerated chicken meatballs

Abstract: The aim of the present study was to evaluate application of Ziziphora clinopodioides essential oil (ZEO) to extend shelf life and control Listeria monocytogenes and Staphylococcus aureus in chicken meatballs. The control and treated samples with different concentrations of ZEO (0.1, 0.2, and 0.3% vol/wt) were preserved at refrigerated temperature for 12 days and analyzed for microbial (total viable count, psychrotrophic bacteria, Pseudomonas spp., Enterobacteriaceae, L. monocytogenes, and S. aureus), chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…Also, various preservatives have been utilized to hinder contamination during production, distribution, and storage as well as to increase shelf life of raw and processed meat and poultry products. Although food-grade and Generally Recognized as Safe (GRAS) synthetic additives have been usually used in the food industry, in recent years, consumers have shown an increasing concern about the use of synthetic chemical preservatives (18)(19)(20). Therefore, there is an increasing tendency in using natural additives including antioxidants, antimicrobials, sweeteners, and coloring agents that originated from animals, plants, and microorganisms (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Also, various preservatives have been utilized to hinder contamination during production, distribution, and storage as well as to increase shelf life of raw and processed meat and poultry products. Although food-grade and Generally Recognized as Safe (GRAS) synthetic additives have been usually used in the food industry, in recent years, consumers have shown an increasing concern about the use of synthetic chemical preservatives (18)(19)(20). Therefore, there is an increasing tendency in using natural additives including antioxidants, antimicrobials, sweeteners, and coloring agents that originated from animals, plants, and microorganisms (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The TVC and PTC were increased in all treatment groups, but the increase in ZEO 2% + LCNF 2% and ZEO 2% + LCNF 1% groups was slower than in all other groups over storage time ( P < 0.05). The notable antimicrobial effect of ZEO could have been responsible for the lower microbial population found in the treated groups in comparison with the untreated sample (Shahbazi, Karami, & Shavisi, 2017). Jridi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Shahbazi et al. (2017) reported that ZEO 0.3% could significantly improve the microbiological property of chicken meatballs at least 12 days under chilled storage condition. Hamedi, Kargozari, Shotorbani, Mogadam, and Fahimdanesh (2017) indicated that chicken fillets coated with sodium alginate and galbanum gum supplemented with Ziziphora persica EO (0.5% and 1%) had TVC and PTC below 7 log CFU/g after 12 days of cooled storage condition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the minor constituents of the EOs were ever indicated to significantly suppress the bacterial growth, and the synergistic effect of these minor compounds in the EOs must also not be ignored (Lv, Liang, Yuan, & Li, 2011). As previously described, ZEO has received remarkable interest owing to its antimicrobial activity on inhibition growth of food-borne pathogens and indigenous bacterial microorganisms in perishable food products and in vitro condition (Hamedi et al, 2017;Mohebi & Shahbazi, 2017;Rezaei & Shahbazi, 2018;Shahbazi et al, 2017;Shavisi et al, 2017). Shahbazi et al (2017) found that ZEO 0.3% could be used for the shelf-life improvement of chicken meatballs without any unpleasant sensory attributes.…”
Section: Effects Of Designated Films On Microbiological Properties mentioning
confidence: 99%